A Theoretical Model of Self-Concept and Self-Esteem in the Foreign Language Classroom - Rubio-Alcalá, Fernando David; Cano-Jiménez, Pablo Antonio (International Journal of English Studies, 2024)
This paper proposes a domain-specific theoretical model of self-concept and self-esteem in the foreign language classroom context. We studied different dimensions and factors, and Confirmatory Factor Analysis (CFA) yielded a three-dimensional structured acceptable model fit with a reliability coefficient of ω= .92 (n=252), supporting the dimensions of language competence, task performance skills, and perceived social support. The specific factors within these dimensions and their interactions were analysed. Implications for research and pedagogy are also discussed.